Development of Acid-Base E-Module Based on Contextual Approach with REACT Strategy to Improve Students’ Learning Outcomes - Azmi, Lutfiah; Latisma, Latisma (FKIP Universitas Lampung, 2022)
This study aims to produce teaching materials in the form of e-modules based on a contextual approach with a REACT (Relating, Experiencing, Applying, Collaborating, Transferring) strategy on acid-base materials.This development is a type of EDR (Educational Design Research) research with a plomp research model. Lecturers and teachers act as expert reviews, and 9 students become research subjects in this development research. The data obtained in the form of content validity, construct, linguistic and graphic data were processed using the AIken's V formula, while the practicality data was processed using practical percent. Based on the results of the study, the V value for content validity was 0.84, construct validity was 0.83, linguistic validity was 0.84 and graphic validity was 0.87, which were included in the valid category. Then the practicality results show a value of 90% with a very practical category and the results of the effectiveness test show that e-modules can improve student learning outcomes Keywords: e-modul, contextual approach, REACT learning strategy, acid baseDOI: http://dx.doi.org/10.23960/jpmipa/v23i1.pp266-275